Of "Marriage" and Other "Bourgeois Rites of Life". The Affirmation Rituals of The Cuban Socio-Economic Elite and Their Representation in the Social Chronicle (1947-1958) - Vázquez Fleitas, Laura (Revista de Historia Social y de las Mentalidades, 2023)
The daily life of men is marked by various rituals that allow them to structure their distinctive practices and delimit the place they occupy in society. The rites of life constitute a form of distinction and exercise of symbolic power used by the elites as emblems of superiority. In the specific case of the Cuban bourgeois elite of the period between 1947 and 1958, these rites are marked by the constant need for exhibition as proof of social position, while the maintenance of that position determines the urgency of ritual staging. In these circumstances, social chronicles became mechanisms for recreating the most distinctive rituals of these subjects as a way of appreciating the dynamics of performance of such a class.
Keywords: Social chronicle; Cuban socioeconomic elite; Life rituals; Social distinction